PENGARUH PRODUK BANK MUAMALAT TERHADAP PERTUMBUHAN U SAHA M IKRO K ECIL M ENENGAH DI KOTA PALOPO - Ayyubi, Mukhtaram (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2016)
This research aims to know and analysis the business capital, investment and consumptive toward small micro and medium growing in Muamalat Syariah Bank Branch of Palopo, and to know and analysis between the product have dominant impact toward small, micro and medium enterprise growing in Muamalat Syariah Bank Branch of Palopo. The result of research to found that the product of Muamalat Syariah Bank such as business capital, investment and consumptive in simultaneous affected in positive and significant toward small, micro and medium enterprise growing at Palopo. And in partial the product have applied to customer as attempt to increase of small, micro and medium growing at Palopo City. Based on the result to found that the business capital have dominant affected positive and significant toward UMKM growing at Palopo. This mean the capital to give from client or customer suitable with appointment which to insurance it, would support increasing the UMKM growing